EXPLORING TOURISM ATTRACTIONS IN OUIDAH, BENIN: VISITOR EXPERIENCES AND RECOMMENDATIONS - T?tar, Corina Florina; Dougnon, Dossou Luc; Sohounnon, Marc; Broutani, Yaya Mora; White, George; Ecer, Zeynep Ceylin (Editura Universitatii din Oradea, 2025)
The aim of the study is to explore visitor experiences and propose strategic improvements for tourism in Ouidah (Benin), a town renowned for its cultural and historical landmarks, including the Route of the Slaves and the Temple of Pythons. Using data collected from an online survey of 105 participants from Benin and abroad, the research highlights the strong appeal of Ouidah’s heritage attractions while identifying critical areas for enhancement, such as infrastructure, accessibility, and promotional efforts. Findings show the Slaves’ Route (24.8%), Python Temple (24.3%), and Gate of No Return (22%) are the most visited, while sites like the Indigo Color Home (3.1%) remain under-visited, indicating the need for better promotion.Word-of-mouth of 46% of respondents was the main information source, followed by miscellaneous sources (36%), while internet and travel agencies played minor roles. Infrastructure was rated mainly “Good” (58%), though issues included poor road conditions, limited public transport, lack of signage, and inadequate amenities such as restrooms and shaded areas. Safety, environmental management, and authenticity of Vodun heritage interpretation were also concerns. A rate of 70% of respondents would “definitely” recommend Ouidah, showing strong potential for repeat and referral tourism. Recommendations include infrastructure upgrades, accessibility improvements, interactive cultural experiences and diversified promotion. The findings emphasize the need for sustainable tourism practices, community engagement, and targeted marketing strategies to strengthen Ouidah’s position as a cultural destination in West Africa. Actionable recommendations are provided to guide policymakers and tourism managers in elevating visitor satisfaction and preserving the town’s unique legacy. Survey results also revealed seasonal peaks in visitation during February, April, July, and August, aligning with school holidays and favoring domestic tourism. The underrepresentation of some niche attractions points to opportunities for thematic circuits and experiential packages. Respondents stressed the need for better guide training, multilingual materials, and eco-friendly site management. Addressing these gaps can extend visitor stay, diversify the tourism offer, and ensure long-term destination resilience. © 2025, Editura Universitatii din Oradea. All rights reserved.
Keywords: Benin; cultural heritage tourism; Ouidah; sustainable destination development; visitor experience